Glycosylation of a Capsule-Like Complex (CLC) by Francisella novicida Is Required for Virulence and Partial Protective Immunity in Mice - Freudenberger Catanzaro, Kelly C.; Champion, Anna E.; Mohapatra, Nrusingh; Cecere, Thomas; Inzana, Thomas J. (Frontiers in Microbiology, 2017)
Francisella tularensis is a Gram-negative bacterium and the etiologic agent of tularemia. F. tularensis may appear encapsulated when examined by transmission electron microscopy, which is due to production of an extracellular capsule-like complex (CLC) when the bacterium is grown under specific environmental conditions. Deletion of two glycosylation genes in the live vaccine strain (LVS) results in loss of apparent CLC and attenuation of LVS in mice. In contrast, F. novicida, which is also highly virulent for mice, is reported to be nonencapsulated. However, the F. novicida genome contains a putative polysaccharide locus with homology to the CLC glycosylation locus in F. tularensis. Following daily subculture of F. novicida in Chamberlain’s defined medium, an electron dense material surrounding F. novicida, similar to the F. tularensis CLC, was evident. Extraction with urea effectively removed the CLC, and compositional analysis indicated the extract contained galactose, glucose, mannose, and multiple proteins, similar to those found in the F. tularensis CLC. The same glycosylation genes deleted in LVS were targeted for deletion in F. novicida by allelic exchange using the same mutagenesis vector used for mutagenesis of LVS. In contrast, this mutation also resulted in the loss of 5 additional genes immediately upstream of the targeted mutation (all within the glycosylation locus), resulting in strain F. novicida Δ1212-1218. The subcultured mutant F. novicida Δ1212-1218 was CLC-deficient and the CLC contained significantly less carbohydrate than the subcultured parent strain. The mutant was severely attenuated in BALB/c mice inoculated intranasally, as determined by the lower number of F. novicida Δ1212-1218 recovered in tissues compared to the parent, and by clearance of the mutant by 10-14 days post-challenge. Mice immunized intranasally with F. novicida Δ1212-1218 were partially protected against challenge with the parent, produced significantly reduced levels of inflammatory cytokines, and their spleens contained only areas of lymphoid hyperplasia, whereas control mice challenged with the parent exhibited hypercytokinemia and splenic necrosis. Therefore, F. novicida is capable of producing a CLC similar to that of F. tularensis, and glycosylation of the CLC contributed to F. novicida virulence and immunoprotection.